Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/pc.24553
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nano‐TiO2/fluorinated polyacrylate core‐shell latex and its application in fabric finishing

Abstract: Nano-TiO 2 /fluorinated polyacrylate hybrid latex was prepared by soap-free emulsion polymerization using reactive emulsifier. With the increase of modified nano-TiO 2 content, the monomer conversion gradually decreased while the gel rate slowly increased accordingly. The transmission electron microscopy (TEM) and dynamic light scattering (DLS) analyses indicated that the core-shell latex particles were uniform with narrow size distribution. In addition, the hybrid film formed from nano-TiO 2 /fluorinated poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The APS content in the control group was the highest, and the Zol width of the control group was 0 mm, indicating that APS had no antifungal activity. In fact, APS can be used as a nitrogen source for a fungal culture. , Additionally, other polymers using APS as an initiator have no significant antimicrobial activity . Therefore, it is reasonable that the control group (containing APS) has no antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The APS content in the control group was the highest, and the Zol width of the control group was 0 mm, indicating that APS had no antifungal activity. In fact, APS can be used as a nitrogen source for a fungal culture. , Additionally, other polymers using APS as an initiator have no significant antimicrobial activity . Therefore, it is reasonable that the control group (containing APS) has no antifungal activity.…”
Section: Resultsmentioning
confidence: 99%
“…40,41 Additionally, other polymers using APS as an initiator have no significant antimicrobial activity. 42 Therefore, it is reasonable that the control group (containing APS) has no antifungal activity. The results of this study indicated that ORP did not determine the antifungal activity of PAH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Over the past decade, a variety of polymeric nanoparticles have been reported in the literature, including polyolefins [11], polyesters [12], polyurethanes [13], polyaryletherketones [14], polysaccharide [15], and polyacrylates [16] as well as their copolymers [16]. Polymeric nanoparticles and their films possess prominent economic value, which are applied for finishing agent [17,18], anticorrosion coating [19], photoresponsive material [20], dielectrics, and adhesives [21].…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 14, the water contact angle of fluorinated copolymer coating with 1 wt% DFMA rises from 80° of the bare copolymer coating composed of BA, MMA and AA (denoted as PBMA) with DFMA content is 0 wt% to 98°, which shows that a small amount of DFMA can change the coating from hydrophilicity to hydrophobicity. Moreover, the water contact angle increases obviously with the increase of DFMA content and reaches a maximum of 105° when DFMA content is 5 wt%, which is ascribed to the increasing fluorinated groups on the surface of the copolymer coating through their migration towards the surface of the coating based on the driving force of lower surface energy 50,51 . However, the water contact angle has not a marked change when DFMA content continue to rise to 8 and 10 wt%.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the water contact angle increases obviously with the increase of DFMA content and reaches a maximum of 105 when DFMA content is 5 wt%, which is ascribed to the increasing fluorinated groups on the surface of the copolymer coating through their migration towards the surface of the coating based on the driving force of lower surface energy. 50,51 However, the water contact angle has not a marked change when DFMA content continue to rise to 8 and 10 wt%.…”
Section: Resultsmentioning
confidence: 99%